Periodical Measurements of VLF Radio Signals and Noise Sounds in Črna Jama (Postojnska Jama) - Kachalin, Igor; Liashchuk, Oleksandr; Šebela, Stanka (Acta Carsologica, 2017)
In Črna Jama, which is part of Postojnska Jama, underground measurement of VLF (Very Low Frequency) radio signals was periodically carried out in 2012 and 2013 for detection of possible pre-seismic and/or other anomalies and to ascertain suitability of VLF monitoring in a natural cave environment. The modulation of the VLF signal was connected with a powerful atmospheric front and changes of the precipitation level. VLF data showed day and night changes and also significant changes between dry and rainy periods when water from the surface reached the cave chamber through about 30 m of limestone roof. During VLF monitoring we did not receive earthquake precursor signals. VLF monitoring in a karst cave could be an option for future research in understanding pre-seismic and other anomalies. On-line connection with other VLF surface or cave monitoring sites in Europe is necessary in future VLF registration. Results of preliminary VLF monitoring showed Črna Jama to be a suitable place for future studies. Key words: VLF radio signals, noise sounds, pre-seismic anomalies, Črna Jama, Slovenia.